THE POLICY IMPLEMENTATION OF NATIONAL STANDARD FOR EDUCATION ON THE IMPLEMENTATION OF THE ELEMENTARY SCHOOL IN WAJO REGENCY - Aminah, Sitti; Ismail, Imran (Acta Scientiae et Intellectus, 2024)
This research aims at describing the stage of the policy implementation of national standards for education, describing the determinant factors which support the policy implementation of national standard, and describing the forms of policy implementation of national standard for education in the implementation of the elementary school of national standard (SDSN) in Wajo regency. The research finding shows that: (1) the stage policy implementation of national standard for education in the implementation of SDSN has been implemented in accordance with the applicable legislation, but it has not been implemented optimally. Among 385 elementary schools, there are only 11 schools which have category SDSN category, (2) the determinant factors which support the policy implementation of national standard for education are content and context of the policy especially infrastructure, educator, content standard, and educational assessment standard, (3) the forms of national standard for education consist of Elementary School motivated to involve in the policy implementation of SD-SN. The policy of SD-SN becomes a supporter for the school to explore the potential of non-governmental. In addition the position of decision-making in the policy implementation of national standard for education in the elementary school is at level of headmaster and education department. Therefore, the motivation and monitoring as a continuous leading is conducted in integrated. The optimization of resources as the component of national standard for education especially for content standard, infrastructure standard, educator standard, and educational assessment standard support the establishment of an effective national education system.